MARKETING AND MUSEUMS IN THE REPUBLIC OF MOLDOVA - Elena PLOȘNIŢA (Academy of Sciences of Moldova, 2014)
The author examines the role and place of a museum in the contemporary society highlighting the need and usefulness of developing and promoting museum marketing policies as an important and even crucial factor for the survival and successful development of any museum. Museums in Moldova do not have the funds for marketing and promotion and experience a lack of specialists in the fi eld of public communication. Despite this, the national museums implement some practices and elements of marketing: marketing research (surveys), regional seminars on museum marketing, projects on the promotion of museums and museum cultural products, etc. The author believes that in today‘s competitive environment quality and quantity of collections can no longer serve as a lifeline for the success of museums. It is necessary to rethink the museum, to implement marketing in the museum activity of the Republic of Moldova.